Quantum transport properties of hybrid BN–C nanotubes: Strong spin filtering effect robust against Stone–Wales defects - Haiqing Wan; Tong Chen; Wei Hu; Yee Sin Ang (APL Materials)
We study the spin-polarized electron transport properties of hybrid BN–C nanotubes (BN–CNTs) in their pristine form and with Stone–Wales defects, namely, Cx(BN)10−x, using combined first-principles density functional theory and quantum transport simulations. We show that the band structures of pristine BN–CNTs can be sensitively tuned by their composition, transiting from the nonmagnetic semiconductor to half-semimetal and finally to a narrow gap semiconductor with increasing x. The spin-dependent current–voltage characteristics are sensitively modulated by x in the hybridized Cx(BN)10−x. The SW defect acts as an active scattering center for BN–CNTs, which decreases the overall conductance of nanotubes. Remarkably, a spin-filtering effect (SFE) with nearly 96% filtering efficiency is observed in C4(BN)6, and such a high SFE remains robust even in the presence of Stone–Wales defects. These results reveal the potential role of hybrid BN–CNT as a building block for spintronic device technology.